Job Lock: Evidence from a Regression Discontinuity Design. Issue 1 (January 2016) - Fairlie, Robert W.; Kapur, Kanika; Gates, Susan
Abstract : Employer‐provided health insurance may restrict job mobility, resulting in "job lock." Previous research on job lock finds mixed results using several methodologies. We take a new approach to examine job lock by exploiting the discontinuity created at age 65 through the qualification for Medicare. Using a novel procedure for identifying age in months from matched monthly Current Population Survey data and a relatively unexplored administration measure of job mobility, we compare job mobility among male workers in the months just prior to turning age 65 to job mobility in the months just after turning age 65. We find no evidence that job mobility increases at the age 65 threshold when Medicare eligibility starts. We also do not find evidence that other factors such as retirement, reduction in hours worked, Social Security eligibility, pension eligibility, and sample changes confound the results on job mobility in the month individuals turn 65.